Biomarkers of Oxidative Stress and Antioxidant Defense - Demirci-Çekiç, Sema; Özkan, Gülay; Avan, Aslı Neslihan; Uzunboy, Seda; Çapanoğlu, Esra; Apak, Reşat (Journal of pharmaceutical and biomedical analysis, 2022)
•In a healthy body, there is a balance between reactive species and antioxidants•When oxidizing species cannot be balanced by antioxidants oxidative stress occurs•Oxidative stress causes a damage on biomacromolecules (DNA, proteins and lipids)•The products formed as a result of these damages are called biomarkers.•The measurement of biomarkers can provide important information about health status A number of reactive oxygen and nitrogen species are produced during normal metabolism in human body. These species can be both radical and non-radical and have varying degrees of reactivity. Although they have some important functions in the human body, such as contributing to signal transmission and the immune system, their presence must be balanced by the antioxidant defense system. The human body has an excellent intrinsic enzymatic antioxidant system in addition to different non-enzymatic antioxidants having small molecular masses. An extrinsic source of antioxidants are foodstuffs such as fruits, vegetables, herbs and spices, mostly rich in polyphenols. When the delicate biochemical balance between oxidants and antioxidants is disturbed in favor of oxidants, “oxidative stress” conditions emerge, under which reactive species can cause oxidative damage to biomacromolecules such as proteins, carbohydrates, lipids and DNA. This oxidative damage is often associated with cancer, aging, and neurodegenerative disorders. Because reactive species are extremely short-lived, it is almost impossible to measure their concentrations directly. Although there are certain methods such as ESR / EPR that serve this purpose, they have some disadvantages and are quite costly systems. Therefore, products generated from oxidative damage of proteins, lipids and DNA are often used to quantify the extent of oxidative damage rather than direct measurement of reactive species. These oxidative damage products are usually known as biomarkers. Determination of the concentrations of these biomarkers and changes in the concentration of protective antioxidants can provide useful information for avoiding certain diseases and keep healthy conditions.